Simplifying
6(7n + -5m) + 8m = 0
Reorder the terms:
6(-5m + 7n) + 8m = 0
(-5m * 6 + 7n * 6) + 8m = 0
(-30m + 42n) + 8m = 0
Reorder the terms:
-30m + 8m + 42n = 0
Combine like terms: -30m + 8m = -22m
-22m + 42n = 0
Solving
-22m + 42n = 0
Solving for variable 'm'.
Move all terms containing m to the left, all other terms to the right.
Add '-42n' to each side of the equation.
-22m + 42n + -42n = 0 + -42n
Combine like terms: 42n + -42n = 0
-22m + 0 = 0 + -42n
-22m = 0 + -42n
Remove the zero:
-22m = -42n
Divide each side by '-22'.
m = 1.909090909n
Simplifying
m = 1.909090909n